MANAJEMEN PRIVASI KOMUNIKASI PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Melita, Yerah; Saputri, Rizka Jihan (Istek Widuri Jakarta, 2024)
This research is motivated by the many cases of violence in Indonesia against women. Women are weak people who are victims of violence, especially in domestic life. Households that have problems and conflicts that cannot be resolved properly and completely result in verbal and physical violence. This research aims to determine the Communication Privacy Management of Women Victims of Domestic Violence (KDRT). The theory used in this research is the Communication Privacy Management theory proposed by Sandra Petronio. This theory is a map of how someone can maintain their privacy. This theory also states that each individual has the right to choose how they want to disclose personal information about themselves to others. To obtain answers from this research, researchers used qualitative research methods with 3 (three) informants using purposive sampling techniques. The data collection techniques used were observation, in- depth direct interviews with informants and making documentation in the form of notes on the results of interviews with informants. The research results show that Communication Privacy Management for Women Victims of Domestic Violence is carried out consciously and with full selective and strict consideration in choosing trusted friends to share their private information with. However, information that is felt to be very personal is often consciously and carefully kept to oneself and kept secret or not disclosed to anyone.